Phenotypic Stability in Sugarcane (Saccharum officinarum L.) Through Different Classical Parametric Measures under Saline-Alkali Condition - Kumar, Anand; Kumar, Amarendra; Parmhansh, P. (International Journal of Bio-resource and Stress Management, 2023)
Fifteen early and mid late sugarcane genotypes were evaluated for their phenotypic stability under four different environments under saline-alkali condition in respect of cane yield and its component characters through different parametric stability models. The stability parameters (X, bi and S2di) for cane yield and its component characters revealed that the genotypes BO 146 was stable in wide range of environments for cane yield and number of millable canes, while, BO 147 and BO 141 were found most stable for cane yield, germination percent at 45 DAP, number of shoots at 120 DAP, number of millable canes in favourable environments and its attributes and less sensitive to environmental change. The genotype BO 110 was showed good germination percent at 45 DAP and number of millable canes in poor environments. The S.F. value nearest to unity for cane yield was observed for BO 146 followed by BO 136, BO 110, BO 144 and BO 109 while, for number of millable canes BO 146 was recorded S.F. value nearest to unity followed by the genotypes BO 110, BO 144, BO 137 and CoP 9702. The estimated ecovalence revealed that the genotypes, BO 139, CoP 022, CoP 9702 and BO 109 showed high mean for cane yield and exhibited low ‘Wi’ values which indicated that these genotypes had contributed minimum towards genotype×environment interaction component. The present investigation revealed that the genotypes, BO 147, BO 146 and BO 136 were identified as better sugarcane varieties for changing environments.